The influence of personality factors on well-being through self-esteem: An Italian-Spanish lexical comparative study. (June 2021) - Fadda, Daniela; Scalas, L. Francesca; Quevedo-Aguado, M. Paz; Benavente Cuesta, María H.
Abstract: Considering the psycholexical approach, this study aimed to test the structure of the Big-five model of personality in Italy and Spain using exploratory structural equation modelling (ESEM) and to use predictive latent models to investigate whether these traits influence hedonic and eudaimonic well-being directly and indirectly, as mediated by self-esteem. ESEM analyses conducted with Italian and Spanish samples, including 400 ( M age  = 21.49, SD  = 2.35; 81.5%female) and 602 ( M age  = 20.52, SD  = 1.93; 81%female) university students, respectively, found that a three-factor solution (Agreeableness, Extraversion, Conscientiousness) showed better model fit and more well-defined factors than either a four- (adding Emotional-stability) or five-factor (adding Integrity) solution. Predictive models using the three-factor solution showed that, in both samples, Extraversion indirectly affected hedonic well-being, global eudaimonic well-being, and Effortful-Engagement; Conscientiousness directly and indirectly affected hedonic well-being, but affected eudaimonic well-being (directly and indirectly) only in the Italian sample. The main difference between samples in relation to Agreeableness was that, in the Italian sample, this trait did not affect self-esteem, but directly promoted hedonic well-being. Thus, a psycholexical three-factor solution appeared more stable across languages; moreover, the results provided initial evidence on the generalisability across samples of the effects of personality traits on well-being, both directly and as mediated by self-esteem. Highlights: The structure of personality traits was tested in an Italian and Spanish sample. The lexical comparative study was carried out within an ESEM approach. A three-factor structure (Agreeableness, Extraversion, Conscientiousness) emerged. Results showed distinctive predictive patterns of personality traits on well-being. Self-esteem mediated the promotion of hedonic and eudaimonic well-being.